Optical code sequences for spectral-amplitude-coding optical CDMA systems - Syed Alwee Aljunid, Syed Junid; M., Ismail; A. R., Ramli; Borhanuddin, M. Ali; Mohamad Khazani, Abdullah (Universiti Malaysia Perlis (UniMAP), 2010)
OPTICAL SPECTRUM code-division multiple-access (OSCDMA) is a multiplexing technique adapted from successful implementation in wireless networks. In OSCDMA each user is assigned with a code sequence code that serves as an address. An optical CDMA user modulates its code / address with each data bit and initiates asynchronous transmission. This modifies its spectral appearance, recognizable only by the intended receiver and is a noise-like bursts for others.